Sediment accumulation and organic material flux in a managed mangrove ecosystem: estimates of land–ocean–atmosphere exchange in peninsular Malaysia - Alongi, D.M.; Sasekumar, A.; Chong, V.C.; Pfitzner, A.; Trott, L.A.; Tirendi, F.; Dixon, P.; Brunskill, G.J. (Elsevier, 2004)
Rates of sediment accumulation and organic matter decomposition in mangrove forests of different age were examined at the Matang Mangrove Forest Reserve in peninsular Malaysia. These data were used with previous findings to construct a first-order mass balance of carbon to determine whether the ecosystem is net heterotrophic or autotrophic, and to estimate land–ocean–atmosphere exchange. Measurements of various carbon and nitrogen processes in sediments suggest that organic matter is rapidly and efficiently mineralized to a depth of 1 m. Rates of total carbon oxidation in sediments (TCOX) ranged from 77 to 118 mmol C m−2 day−1 with no significant differences with forest age. Sulfate reduction (range: 19–53 mmol S m−2 day−1) appeared to be the dominant decomposition pathway, accounting for an average of 51–75% of sediment TCOX. Aerobic respiration (range: 5–20 mmol C m−2 day−1) accounted for ≈5–20% of mean TCOX. Methanogenesis was not measurable. Denitrification (range: 0.4–11.0 mmol N2 m−2 day−1) was rapid but very variable, and may have accounted for ≈25% of TCOX at the old-growth forest. Rates of sediment mass accumulation (range: 2.2–11.4 kg m−2 year−1) were rapid compared with previous measurements in mangroves. Efficiency of carbon burial (range: 23–29 mmol C m−2 day−1) in sediments increased from 16% to 27% from the youngest to the oldest forest. The ratio of sediment TCOX to mangrove net primary production decreased from 28% to 7% with increasing forest age. The efficiency of N mineralization (range: 67–81%) and burial (range: 10–29%) in sediments showed the opposite pattern. Tree N demand required from 8 to 22 mmol N m−2 day−1. Surface N2 fixation was measurable only in two of six trials, but was rapid (range: 2.3–3.0 mmol N2 m−2 day−1). A mass balance of carbon for the entire reserve suggests that the ecosystem is currently net autotrophic, with a net ecosystem production of ≈21×109 mol C year−1 and an ecosystem P/R of 1.4. Despite considerable uncertainty, forest production and respiration clearly dominates carbon flow, accounting for ≈95% of total inputs and ≈79% of total outputs, respectively. River inputs, phytoplankton primary production and trash fish inputs to fish cage aquaculture in the waterways were comparatively minor. Export of mangrove detritus equated to 25% of net canopy production; only 2% of total carbon input to the ecosystem was buried in mangrove sediments. Clear felling and thinning of forests accounted for <1% of total outputs; 73% of total carbon inputs to the ecosystem were respired. Our budget indicates that the major exchange of carbon in this managed ecosystem is between forest and atmosphere.